Does Hemoglobin mass increase with several years of endurance training? - A cross-sectional study with U18, U23 and elite national team cyclists - Wehrlin, J. P.; Clenin, G. E. (14th annual Congress of the European College of Sport Science, Oslo/Norway, June 24-27, 2009, Book of Abstracts, 2009)
Introduction: It is unclear if haemoglobin mass (Hbmass) and red cell volume (RCV) increase with several years (ys) of training in endurance athletes (Sawka et al., 2000, Heinicke et al., 2001, Prommer et al., 2008). Especially, little is known about changes between junior and adult age. The aim of this study was to determine with a cross-sectional approach, whether national team endurance athletes in the age-related teams `under 18` (U18), `under 23` (U23) and `elite` (>23 ys) are characterized by different Hbmass, RCV, plasma volume (PV) and blood volume (BV). Methods: Blood volume parameters (CO-rebreathing method) and other blood, iron, performance and training parameters were measured in each a group of U18 (age = 16.9 ± 0.6ys; n = 15), U23 (age = 19.2 ± 1.2ys; n = 13) and elite (age = 27 ± 4.2ys; n = 14) male Swiss national team cyclists (road, cross-country and track). Results: There were no differences in either body weight related Hbmass (U18 = 14.4 ± 1.2g/kg; U23 = 14.0 ± 1.3g/kg; elite = 14.6 ± 1.0g/kg), RCV (40.4 ± 3.4; 39.2 ± 3.9; 40.8 ± 3.2 ml/kg), PV (63.6 ± 7.1; 64.6 ± 7.1; 64.6 ± 8.1 ml/kg) and BV (104.1± 8.6; 103.8 ± 9.8; 105.4 ± 10.2 ml/kg) or absolute values. Absolute power at 4mmol/l blood lactate in the lactate threshold test was lower in the U18 than in the elite group (p = 0.043) whereas differences in maximal absolute power output did not reach statistical significance (p = 0.102). Training hours per week were lower (p = 0.032) in U18 than in the elite athletes. Discussion: Our results indicate that several years of endurance training between the U18 and the elite age in national team cyclists do not increase Hbmass, RCV, PV and BV, but power at 4mmol/l blood lactate concentration. Interestingly, in another recent cross-sectional study with XC-skiers and triathletes (Steiner, Boutellier & Wehrlin, 2009), we found Hbmass to be lower at age 16 than at age 21 while it was similar at age 21 and 28. Perhaps, Hbmass can increase with endurance training in athletes younger than 17ys? However, when interpreting our results, one has to take into account, that although all our subjects where national team athletes, we used a crosssectional design. This implies the risk of a possible selection bias. Studies with a longitudinal design are needed. Conclusion: Hbmass can be similar in male U18, U23 and elite national team cyclists, what suggests, that Hbmass does not increase with several years of endurance training in athletes from the U18, to the U23 and the elite national team.